Electronic transport through single conjugated molecules - Weber, Heiko B.; Reichert, Joachim; Weigend, Florian; Ochs, Rolf; Beckmann, Detlef; Mayor, Marcel; Ahlrichs, Reinhart; von Löhneysen, Hilbert (Chemical Physics, 2002)
We investigate electronic transport through single conjugated molecules, and compare our data to results of quantum chemical calculations. Conductance spectra of two types of molecules are studied in a metal-molecule-metal junction established using the mechanically controlled break-junction technique. We observe a suppressed conductance at low bias, characteristic step-like features at higher voltages, and strong sample-to-sample fluctuations. We develop a quantum-chemical model for our system using DFT calculations, with the electrodes modelled by small clusters. We consider the effects of different geometries of molecule-metal configurations and bonding as well as finite electric field, and are thereby able to account for the phenomenology of the experimental data. (C) 2002 Elsevier Science B.V. All rights reserve
UnivIS-Import:2017-11-07:Pub.2002.nat.dphy.IAP.LAP.electr_4